COLLABORATIVE WRITING: STRATEGI MENINGKATKAN KETRAMPILAN MENULIS DALAM PEMBELAJARAN GENRE-BASED WRITING - Intan Permata Hapsari (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2011)
This is a classroom action research within the context of Systemic Functional Linguistics, which is conducted to investigate how hortatory exposition texts are developed through rhetorical development systems, and how these systems of rhetorical development are realized in the clauses for their moves and steps. The study was done towards a class of Genre-based Writing in English Department of UNNES. The main goal of this study is to help students improve the way how to communicate their meanings through texts they develop. The problems which the writer deals with to uncover the above phenomena are: (1) How can collaborative writing technique helps students in solving problems dealing with writing and developing thesis statement in Hortatory Exposition? And (2) how does collaborative writing technique help students achieve the goals of the Genre-based Writing Subject, especially in achieving the goal of the teaching of Hortatory Exposition? Based on the result of the research, it is found that there is a positive impact on the use of collaborative writing technique on the teaching and learning process of Hortatory Exposition text. This can be seen on the result of the evaluation of the process and of the composition produced by students during the research. The students’ writings from the four cycles improve significantly.